Information security and countering disinformation in complex crisis environments - Krupa, Elvin (Global Prosperity, 2023)
Abstract. When reality cracks at the seams and the flow of information turns into a destructive tsunami... what is a person left with? Doubt. Panic. And a complete loss of direction. The author of this article argues that this is precisely the main goal of modern disinformation — not to convince, but to break the ability to think. It's a weapon that targets not bodies, but consciousness, destroying trust and turning society into a disoriented crowd. Old methods of defense, like censorship, look naive in this new world. It's like trying to stop a flood by building a dam out of sand. That's why this work proposes a radically different approach. The author presents their own concept — a comprehensive, three-tiered architecture for information defense. This isn't just a collection of disparate measures. It's an attempt to create a holistic, resilient mechanism. How does it work? First — technology. The analytical level, which uses AI for early threat detection, serves as our "eyes and ears." Then — communication. Creating unified coordination centers that speak with one, honest voice is our "nervous system." And finally, the deepest level — the cognitive one. This is about training the public in media literacy, forming a "collective immunity" to manipulation. This is our "psychological shield." The underlying idea is to create "information sterility." This isn't about a vacuum. It's more about creating an "immune system" for society. An ecosystem where truthful, verified information spreads quickly and earns trust, while fakes and manipulations, on the contrary, get bogged down, failing to go viral. This changes the very paradigm of the fight: not chasing lies, but getting ahead of them. Ultimately, the proposed model is not just a set of defensive measures. It's a philosophy of proactive resilience. It proves that in the modern world, information security is not the job of separate agencies. It's a collective effort. An effort of technologists, communicators, educators, and every conscious citizen.